Genome diversity, recombination, and virulence across the major lineages of Paracoccidioides - Muñoz, José F.; Farrer, Rhys A.; Desjardins, Christopher A.; Gallo, Juan E.; Sykes, Sean; Sakthikumar, Sharadha; Misas, Elizabeth; Whiston, Emily A.; Bagagli, Eduardo [UNESP]; Soares, Celia M.A.; Teixeira, Marcus de M.; Taylor, John W.; et al. (American Society for Microbiology, 2016)
The Paracoccidioides genus includes two species of thermally dimorphic fungi that cause paracoccidioidomycosis, a neglected health-threatening human systemic mycosis endemic to Latin America. To examine the genome evolution and the diversity of Paracoccidioides spp., we conducted whole-genome sequencing of 31 isolates representing the phylogenetic, geographic, and ecological breadth of the genus. These samples included clinical, environmental and laboratory reference strains of the S1, PS2, PS3, and PS4 lineages of P. brasiliensis and also isolates of Paracoccidioides lutzii species. We completed the first annotated genome assemblies for the PS3 and PS4 lineages and found that gene order was highly conserved across the major lineages, with only a few chromosomal rearrangements. Comparing whole-genome assemblies of the major lineages with single-nucleotide polymorphisms (SNPs) predicted from the remaining 26 isolates, we identified a deep split of the S1 lineage into two clades we named S1a and S1b. We found evidence for greater genetic exchange between the S1b lineage and all other lineages; this may reflect the broad geographic range of S1b, which is often sympatric with the remaining, largely geographically isolated lineages. In addition, we found evidence of positive selection for the GP43 and PGA1 antigen genes and genes coding for other secreted proteins and proteases and lineage-specific loss-of-function mutations in cell wall and protease genes; these together may contribute to virulence and host immune response variation among natural isolates of Paracoccidioides spp. These insights into the recent evolutionary events highlight important differences between the lineages that could impact the distribution, pathogenicity, and ecology of Paracoccidioides.
Keywords: Evolution; Genetic recombination; Genome analysis; Mycology; Paracoccidioides; Population genetics